Efforts to Increase Regional Original Income Through Land Value Zone in Merauke District - Yacobus, Romi; Ariyanto, Ariyanto (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Regional legal products are regulations established by the regional government and the Regional People's Representative Council (DPRD), for example regional regulations, regional head regulations and/or other regulations issued by the Regional Government. The Decree of the Merauke Regent regarding the Determination of Land Value Zones and Selling Value of Land Objects was a decision issued to increase the local revenue of Merauke Regency, but in reality there is still a legal vacuum so that the benefits and sense of justice in society have not been fulfilled. Therefore, the local government and DPRD can review and be encouraged to become a Regional Regulation and/or Regional Head Regulation. This study aims to: (know the legal structure in an effort to increase local revenue through land value zones in Merauke Regency.